Construction of ecological security pattern in national land space from the perspective of the community of life in mountain, water, forest, field, lake and grass: A case study in Guangxi Hechi, China. (June 2022) - Gao, Mengwen; Hu, Yecui; Bai, Yuping
Graphical abstract: Highlights: Based on the circuit theory, we constructed Hechi's ecological security pattern. Maximum eco-economic benefits are achieved when 7000 as the resistance threshold. The ecological pattern of "three axis, five belts, six zones, multiple cores" is proposed. The concept of "Mountain, Water, Forest, Field, Lake and Grass" guides restoration. The research results can guide ecosystem protection management of karst areas. Abstract: Under the influence of global ecosystem changes, the coordinated development of all natural elements has become a top priority in maintaining ecological security. In this context, China has put forward the concept of "mountain, water, forest, field, lake and grass as a community of life", with a systemic thinking and holistic concept to promote spatial protection and restoration of the national territory. This study uses the logical line of "Diagnosing the all-natural elements base - Guarding the natural security boundaries- Integrated conservation and restoration of natural elements" to comprehensively construct a spatial ecological security pattern in the typical karst area of Hechi, China. We extract ecological sources based on ecosystem service functions and ecological sensitivity. And then considering the effects of both habitat quality and anthropogenic activities to construct ecological resistance surface. The key ecological elements such as ecological corridors, pinch points and barriers are identified according to circuit theory, and the ecological conservation and restoration pattern of mountain, water, forest, field, lake and grass is optimized on the basis of the ecological security pattern, identifies priority areas for protection and restoration, delineates ecological control zones and proposes zoning strategies for ecological control. The study shows that there were 22 ecological sources in Hechi, covering an area of 4886.40 km 2, accounting for 14.59% of the study area, mainly distributed in areas with higher habitat quality, such as the west and south; Using 7000 as the cumulative resistance threshold, 34 ecological corridors were identified with an area of 1873.19 km 2, radiating in a spider web pattern across the whole area; 32 pinch points, mostly concentrated in the northeastern region, and identified barriers covering an area of 1, 966.91 km 2, which is the focus of future restoration. And constructed the ecological conservation and restoration pattern of "three axis, five belts, six zones and multiple cores". The results of the study can provide scientific guidance for the protection of ecological security in the ecologically fragile areas of karst and the comprehensive restoration and management of regional ecosystems, which are of great significance for the sustainable development of global ecosystems.